Perspectives on preconception care in Ethiopia: Social, cultural, and structural determinants - Yared Asmare Aynalem; Pauline Paul; Zohra S. Lassi; Salima Meherali (PLoS ONE, 2026)
Background Although Ethiopia introduced its first national preconception care (PCC) guideline in 2024, PCC remains rarely integrated into routine practice, and existing studies have largely focused on women’s knowledge and behaviors. Little is known about how adults navigate PCC within broader social, cultural, and structural contexts. This study provides an in-depth urban Ethiopian analysis of how adults experience and negotiate PCC within intersecting gender, moral, and institutional systems, offering insights beyond individual-level understanding. Methods An interpretive description design guided semi-structured interviews with 18 adults (10 women, 8 men; 19–45 years) recruited through maximum-variation sampling from two public hospitals in Addis Ababa. Interviews were conducted in Amharic, transcribed, translated, and analyzed inductively. Data analysis was guided by ID principles, complemented by thematic analysis techniques informed by grounded theory, including line-by-line coding, constant comparison, and analytic memoing. Field notes captured contextual and relational dynamics. Results Seven interrelated themes highlighted complex dynamics in PCC. Knowledge was fragmented and often recognized only after complications, shaped by marital gatekeeping, faith-based beliefs, and exclusion of unmarried women. PCC was valued as protective and morally significant, but stigma, poverty, staff shortages, and inconsistent services constrained practice. Men were largely financial supporters, though many expressed a desire to participate, limited by gender norms and women-centered services. Pharmacies and digital media provide informal but sometimes unsafe guidance. Emotional experiences, fear, guilt, secrecy, and hope were central to PCC engagement. Education, peer influence, schools, and community leaders emerged as catalysts for uptake, yet participants emphasized that sustainable PCC required visible institutional support, reliable services, and government recognition. Strategies to enhance practice included simplifying communication, creating accessible clinic entry points, and mobilizing community networks to normalize pre-pregnancy preparation. Conclusions This study reveals PCC in urban Ethiopia as a socially negotiated, morally contested, and structurally uneven practice, far more complex than knowledge deficits imply. These findings offer novel, actionable direction for implementing Ethiopia’s PCC guideline through visible, inclusive, relational, and community-anchored approaches that address the social conditions shaping PCC access.